Nutrition in Pregnancy - Volume II - Timothy R.H. Regnault (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Maternal nutrition during pregnancy is of considerable interest to women, their partners and their health care professionals. In developing countries, maternal undernutrition is a major concern. However, with the increased prevalence of abundant high calorie diets, their impact upon pregnancy outcome is of concern. In addition to the amount of nutrition available and its macronutrient composition within a diet, there is emerging evidence highlighting important roles for the lesser studied micronutrients. Added to this complexity is the distinction between maternal and fetal nutrition and the impact the placenta plays in nutrient metabolism and overall nutrient supply to the fetus. Together, these many variables contribute to placental development and function, fetal growth, and, where placental/fetal nutrition and growth is compromised, through poor maternal diet, and/or diet induced alterations in placental metabolism, the impact is dramatic and can lead to lifelong implications for the offspring. This Special Issue book aims to highlight research in many of these areas.